1996
DOI: 10.1002/(sici)1097-0215(19960927)68:1<75::aid-ijc14>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Interferons induce normal and aberrant retinoic-acid receptors type α in acute promyelocytic leukemia cells: Potentiation of the induction of retinoid-dependent differentiation markers

Abstract: Q 1996 Wiley-Liss, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

1997
1997
2004
2004

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…G-CSF and IFNs were reported to potentiate differentiation of AML cells. 42,43 Like GM-CSF, the two cytokines signal through the Jak/Stat pathway 44 that could be augmented by SS. 25 The existence of such potential interactions is being examined in our ongoing studies.…”
Section: Discussionmentioning
confidence: 99%
“…G-CSF and IFNs were reported to potentiate differentiation of AML cells. 42,43 Like GM-CSF, the two cytokines signal through the Jak/Stat pathway 44 that could be augmented by SS. 25 The existence of such potential interactions is being examined in our ongoing studies.…”
Section: Discussionmentioning
confidence: 99%
“…Analogs of cAMP (8 -12), interferons (13)(14)(15), granulocyte colony-stimulating factor (16), and a novel class of experimental compounds, bis-indols (17), enhance the cytodifferentiating activity of ATRA in AML cell lines. Enhanced cytodifferentia-tion by combinations of bis-indols and ATRA translates into a therapeutically significant effect, as assessed in animal models of APL (17).…”
mentioning
confidence: 99%
“…33,34 It has been shown that IFNs induce retinoic acid receptors in acute promyelocytic leukemia cells and cooperate with RA to overcome the resistance of cells to RA. 36,52 Also RA activates interferon regulatory factor-1 gene expression in promyelocytic leukemia cells. 53 Our results suggest that IFNs together with RA potentiate the effect of RA on uPA and uPAR production and plasmin formation.…”
Section: Discussionmentioning
confidence: 99%